Probabilistic life cycle costing: A case study of centrifugal pumps - Mokhtar, A.A. (Springer Verlag, 2019)
Life cycle costing (LCC)has been gaining attention in industries as a decision-making tool for the management of assets. LCC is generally recognized as a valuable tool in making an optimal decision considering the total cost of ownership rather than just the initial acquisition cost. The deterministic LCC model is commonly used in many plants; however, the deterministic model only inherently encompasses uncertainty factors, i.e., the economic issue alone, and cannot practically and effectively handle the ambiguous other uncertainties such as changes in interest rate, cost of production loss per hour due to unexpected failure, and labor cost per failure, to name a few. The life cycle cost of a repairable system is closely linked to and highly influenced by its maintenance cost which includes its reliability, maintainability, and maintenance support. Thus, to incorporate these uncertainties into LCC, one needs to consider the application of the reliability engineering principles to evaluate the probabilistic nature of the equipment failures and repairs. Â© The Author(s), under exclusive licence to Springer Nature Singapore Pte Ltd. 2019.